The Mundell-Fleming model and macroeconomic stabilization policies - Erico Wulf Betancourt; Ryszard Piasecki (Comparative Economic Research. Central and Eastern Europe, 2023)
This paper analyzes the fiscal policy implications set in the Mundell-Fleming (M-F) model and its effectiveness in emerging economies. It also widens the scope of the policy mix with alternative exchange rates. The empirical evidence about the economies of Chile (1991-2003) and Colombia (1994-2004), about institutions, fiscal policy rule, and the eurozone conditions (1999), were considered relevant The paper has three sections a. The budget-surplus fiscal policy rule and policy effectiveness, b. The role of institutions in setting policy rules, c. The experience of the Chilean and Colombian economies concerning fiscal policy rules within the M-F framework. The main conclusion is that as long as country risk is lower due to countercyclical fiscal policy rules, governments have an alternative means of getting funds at a lower international interest rate. The fiscal policy effect on GDP (output)becomes positive.
Keywords: 330; policy rules; monetary policy autonomy; fiscal policy setting